PENDIDIKAN KEWIRAUSAHAAN: SEBUAH ALTERNATIF MENGURANGI PENGANGGURAN TERDIDIK DAN PENCEGAHAN KORUPSI - Hillyati Mila (AT-TA'LIM, 2013)
The inbalanced numbers of job seekers and the job available as well as the high percentage of corruption in Indonesia has encouraged the government to find solution.    Based on the values promoted by education of entrepreneurship, the government has shifted the Indonesian people from being ‘job seeker’ to ‘job maker’ and prevent corruption.  Whenever the society understand and hold or conduct the entrepreneurship, corruption will decline because the society has already self sufficient and do not rely on the government any more.  Higher education serve the tool for the government to grow and develop students’ character, therefore, this institution is targeted to produce new entrepreneurship. Copyright © 2013 by Al-Ta'lim All right reservedDOI: 10.15548/jt.v20i3.44